The role of cGMP on adenosine A1 receptor-mediated inhibition of synaptic transmission at the hippocampus - Isa ePinto; André eSerpa; Ana Maria Sebastião; Ana Maria Sebastião; José Francisco Cascalheira; José Francisco Cascalheira (Frontiers Media S.A., 2016)
Both adenosine A1 receptor and cGMP inhibit synaptic transmission at the hippocampus and recently it was found that A1 receptor increased cGMP levels in hippocampus, but the role of cGMP on A1 receptor-mediated inhibition of synaptic transmission remains to be established. In the present work we investigated if blocking the NOS/sGC/cGMP/PKG pathway using nitric oxide synthase (NOS), protein kinase G (PKG) and soluble guanylyl cyclase (sGC) inhibitors modify the A1 receptor effect on synaptic transmission. Neurotransmission was evaluated by measuring the slope of field excitatory postsynaptic potentials (fEPSPs) evoked by electrical stimulation at the hippocampal slice. N6-cyclopentyladenosine (CPA, 15nM), a selective A1 receptor agonist, reversibly decreased the fEPSPs by 54%±5%. Incubation of the slices with an inhibitor of NOS (L-NAME, 200μM) decreased the CPA effect on fEPSPs by 57% ± 9% in female rats. In males, ODQ (10 μM), an sGC inhibitor, decreased the CPA inhibitory effect on fEPSPs by 23% ± 6%, but only when adenosine deaminase (ADA,1U/ml) was present; similar results were found in females, where ODQ decreased CPA-induced inhibition of fEPSP slope by 23% ± 7%. In male rats, the presence of the PKG inhibitor (KT5823, 1nM) decreased the CPA effect by 45.0%±9%; similar results were obtained in females, where KT5823 caused a 32%±9% decrease on the CPA effect. In conclusion, results suggest that the inhibitory action of adenosine A1 receptors on synaptic transmission at hippocampus is, in part, mediated by the NOS/sGC/cGMP/PKG pathway.